Hundred years of Botany at the NWU: contributions towards understanding plant and algae function, diversity and restoration in a changing environment - Cilliers, S.S.; Janse van Vuuren, S.; Kellner, K.; Krüger, G.H.J.; Struwig, M.; van Niekerk, C.J.G; Siebert, S.J. (African Biodiversity & Conservation, 2021)
The Department of Botany on the Potchefstroom Campus (formerly Potchefstroom University for Christian Higher Education) of the North-West University (NWU) had its centenary in 2020. In this paper we celebrate this milestone by giving an overview of the history of the Department at this campus, including its recent establishment and expansion on the NWU Mahikeng Campus (formerly the University of North-West). A brief overview is presented of the advances in teaching and research over the years, and the development and relevance of the important plant collections in the botanical garden, two herbaria and the national diatom collection. The main emphasis of this contribution is, however, a reflection on the advancement and significance of research conducted by various disciplines on plant and algae function, diversity and ecological restoration over the years. The different disciplines in Botany at NWU, from the oldest to the more recent, are Plant Taxonomy, Plant Ecophysiology, Terrestrial Plant Ecology, Aquatic Sciences, Urban and Settlement Ecology, Geoecology, and Proteomics. Different aspects contributing to changes occurring in the environment, such as pollution, land degradation, urbanisation, overexploitation of resources and the subsequent effect of these on plant diversity and function are especially addressed in our current research. The results of our research inter alia led to solutions for problems occurring in the landscape and contribute to the well-being of the people using the land and water by restoring important ecosystem services.